Development of Mathematics E-Module Using Kodular and Flipbook for Junior High School Students: Differences - Tri Nova Hasti Yunianta; Tatang Herman; Banu Al Wizhar; Muhammad Al Falah Kurniawan (Universitas Syiah Kuala, 2023)
To develop media such as e-modules, a comprehensive understanding of the applications used to create them is necessary. It is essential to comprehend the features of using e-module applications to ensure their effectiveness in the development of superior e-modules in the future. The objectives of the present study were showing that mobile learning by e-module using different applications, i.e. Kodular and Flipbook, are valid, practical, effective and finding differences between the characteristics of e-module development to get a comprehensive idea for future development for researchers who want to develop e-module using both applications. The present study is a research and development study. The selected development model was ADDIE i.e. Analyze, Design, Development, Implementation and Evaluation. The Subject e-module learning media users were junior high school students. The validity of e-module media by Kodular is 92.55%, which is very good. The validity of e-module media by Flipbook is 90.35%, which is very good. The test result on the respondents who used e-module by Kodular is 83.45% feasible to use and the result of e-module by Flipbook is 86.39% also feasible to use. The Kodular e-module had an average student learning outcome score of 78.28, while the Flipbook e-module had an average score of 70.67. The two e-modules from the application were examined, and five differences were identified in the characteristics of e-modules from Kodular and Flipbook, in order to support the continuous development of e-modules.